American inequality and its consequences - Gary Burtless; Christopher Jencks (Luxembourg Income Study (LIS), 2003)
Income inequality has risen sharply in the United States over the past generation, reaching levels not seen since before World War II. But while almost two-thirds of Americans agree with the statement that 'income differences in the United States are too large', policies aimed at reducing income differences command relatively little popular support. In most rich countries sizeable majorities 'agree strongly' that the government ought to guarantee each citizen a minimum standard of living. Only one American in four agrees strongly with this proposition. The same pattern holds in Congress, where legislators show little interest in policies aimed at taxing the rich, raising the wages of the poor, taxing inherited wealth, or guaranteeing shelter and health care to all Americans. The first three sections of this paper describe how the distribution of income has changed in the United States since the 1970s, why it changed, and why it is more unequal than the distribution in other rich democracies. We then assess the evidence on whether changes in economic inequality affect four other things that Americans care about - economic growth, equality of opportunity for children, longevity, and the distribution of political influence. Section 4 concludes that inequality probably does not have a consistent effect, either positive or negative, on economic growth in rich democracies. Section 5 shows that college attendance became more related to parental income as economic inequality increased in the United States, but it does not find much evidence that a father's economic status has had more influences on his children's economic prospects in the United States than in other rich countries where incomes were more equal. Section 6 argues that increases in economic inequality probably slow the rate of improvement in longevity, but the effect is very small. Thus, we conclude that rising inequality may have lowered life expectancy, but only by a few months. Section 7 discusses the impact of economic inequality on the distribution of political power, arguing that increases in economic inequality tend to increase the political power of the rich, at least in the United States. We conclude by arguing that since the effects of inequality on economic growth, health, and equality of opportunity are modest and uncertain in rich countries, these countries should decide how much economic inequality they are willing to tolerate largely on the basis of what they think is just.
Keywords: 330; Einkommensverteilung; Disparitätsmaß; USA